(untitled) (Tribhuvan University Journal, 2017)
Along with right to food, shelter and education, children have also right to primary health regardless to their sex. Though the Government of Nepal has achieved the goal for reducing child mortality related to Millennium Development Goal. However still a large numbers of children especially girls are deprived of rights to health. This study is based on the oral reporting of purposively selected 269 parents including father and mother. Kathmandu Metropolitan city was taken into consideration during the year of 2013 to 2015. This study reveals that, more parents take their son to private health institutions and daughters to governmental health institutions. Similarly, this study has taken some socio-economic variables related to discrepancy of their son and daughter.